A Breakthrough in Understanding the Pathogenesis of Molar Hypomineralisation: The Mineralisation-Poisoning Model - Hubbard, Michael J.; Mangum, Jonathan E.; Perez, Vidal A.; Williams, Rebecca (Frontiers in Physiology, 2021)
Popularly known as "chalky teeth", molar hypomineralisation (MH) affects over 1-in-5 children worldwide, triggering massive amounts of suffering from toothache and rapid decay. MH stems from childhood illness and so offers a medical-prevention avenue for improving oral and paediatric health. With a cross-sector translational research and education network (The D3 Group; thed3group.org) now highlighting this global health opportunity, aetiological understanding is urgently needed to enable better awareness, management and eventual prevention of MH. Causation and pathogenesis of "chalky enamel spots" (i.e. demarcated opacities, the defining pathology of MH) remain unclear despite 100 years of investigation. However, recent biochemical studies provided a pathomechanistic breakthrough by explaining several hallmarks of chalky opacities for the first time. This article outlines these findings in context of previous understanding and provides a working model for future investigations. The proposed pathomechanism, termed "mineralisation poisoning", involves localised exposure of immature enamel to serum albumin. Albumin binds to enamel-mineral crystals and blocks their growth, leading to chalky opacities with distinct borders. Being centred on extracellular fluid rather than enamel-forming cells as held by dogma, this localising pathomechanism invokes a new type of connection with childhood illness. These advances open a novel direction for research into pathogenesis and causation of MH, and offer prospects for better clinical management. Future research will require wide-ranging inputs that ideally should be coordinated through a worldwide translational network. We hope this breakthrough will ultimately lead to medical prevention of MH, prompting global health benefits including major reductions in childhood tooth decay.